Towards triple elimination of HIV, syphilis and HBV mother-to-child transmission: Protocol of a simplified and integrated strategy in Burkina Faso and The Gambia: Protocol for the phase 1 of the TRI-MOM project - Erwan Vo-Quang; Alice N. Guingané; Lauren Périères; Gibril Ndow; Victor Some; Sheriff Badjie; Asta Jobe; Clarisse Gouem; Yusuke Shimakawa; Dramane Kania; Maud Lemoine; Sylvie Boyer (PLoS ONE, 2026)
Introduction Mother-to-child transmission (MTCT) of HIV, syphilis, and hepatitis B virus (HBV) commonly observed in the WHO African region is associated with excess morbidity and mortality. Despite some progress, the coverage of interventions to prevent MTCT of these infections remains insufficient, particularly for syphilis and HBV. To fulfil these gaps and achieve the triple elimination of MTCT of these infections by 2030, the World Health Organization (WHO) advocates for integration of prevention of MTCT (PMTCT) activities for HBV with HIV and syphilis antenatal services. In partnership with the local governments, the TRI-MOM project, conducted in 2 phases, aims to evaluate a simplified (based on inexpensive rapid diagnostic tests), integrated (in maternal and child health services) and coordinated (between the various programs and health care workers) strategy for the triple elimination of HIV, syphilis and HBV MTCT in Burkina Faso and The Gambia. Methods and analysis The strategy will be implemented in 5 rural and urban health facilities in each country and will include four activities: i) training sessions for healthcare workers working in maternal and child health services, ii) screening of pregnant women of the three infections using rapid diagnostic tests at the first antenatal visit, iii) clinical assessment and treatment of women tested positive for any of the 3 infections, and iv) raising awareness on HIV, Syphilis and HBV PMTCT among pregnant women and empowering those screened positive. 17,000 pregnant women are expected to be screened. The strategy will be evaluated through an interdisciplinary, mixed-methods approach comprising three studies: i) a quantitative and qualitative cross-sectional study conducted both before and after the implementation of the strategy to assess its impact on triple screening coverage in pregnant women; ii) a an intervention study with longitudinal follow-up of pregnant women positive for any of the three infections to assess the coverage of PMTCT measures; and iii) a cost and cost-effectiveness analysis of the project compared to the reference situation in each country, which will rely on a micro costing study to estimate the incremental cost of the strategy per mother/child couple compared with the reference situation in each country, and compare it to the number of avoided infections. Ethics and dissemination The study protocol has been approved by the competent authorities of the countries participating to the research (the LSHTM/MRCUG Scientific Coordinating Committee, the Gambia Government/MRC Joint Ethics Committee, the LSHTM ethics committee, the Burkinabe National Ethical Committee for Research in Health and the French Commission on Information Technology and Liberties). Results on the feasibility and acceptability of the triple elimination strategy will be disseminated using different media including policy briefs, posters and articles. Trial registration number ClinicalTrials.gov NCT05951751 .